AKTIVITAS HASIL BELAJAR SISWA DALAM IMPLEMENTASI KURIKULUM MERDEKA PADA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Putri Wijaningsih Suparjan; Heru Purnomo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The Merdeka Curriculum as an alternative curriculum for overcoming learning setbacks during the pandemic provides the freedom of "Freedom to Learn". This research was conducted at SD N Adiwarno with the aim of identifying and obtaining information about student learning outcomes in the implementation of the independent curriculum in elementary schools. This study uses a qualitative descriptive research design aimed at knowing student learning outcomes in the implementation of the independent curriculum conducted by mathematics teachers in elementary schools. Problems with student learning outcomes studying mathematics using an independent curriculum, namely the lack of creative innovation in developing methods, models, media, mathematics are considered difficult by students, the teacher's way of teaching is monotonous. The results of this study indicate that SDN Adiwarno applies the Merdeka Curriculum to grades 1 and 4 and the rest use the 2013 curriculum. Using the independent curriculum makes learning implemented effectively, even though it has only been implemented for one year.